Ancient Mitochondrial Capture as Factor Promoting Mitonuclear Discordance in Freshwater Fishes: A Case Study in the Genus Squalius (Actinopterygii, Cyprinidae) in Greece - Perea, Silvia; Vukić, Jasna; Šanda, Radek; Doadrio, Ignacio (PLOS ONE, 2016)
Hybridization and incomplete lineage sorting are common confounding factors in phylogeny and speciation resulting in mitonuclear disparity. Mitochondrial introgression, a particular case of hybridization, may, in extreme cases, lead to replacement of the mitochondrial genome of one species with that of another (mitochondrial capture). We investigated mitochondrial introgression involving two species of the cyprinid genus Squalius in the western Peloponnese region of Greece using molecular and morphological data. We found evidence of complete mitochondrial introgression of Squalius keadicus into two populations recognized as Squalius peloponensis from the Miras and Pamissos River basins and a divergence of mitochondrial genomes of S. keadicus from the Evrotas basin from that of the introgressed populations dating from the Pleistocene. Secondary contact among basins is a possible factor in connection of the species and the introgression event. Morphological analyses support the hypothesis of mitochondrial introgression, as S. keadicus was different from the other three populations recognized as S. peloponensis, although significant differences were found among the four populations. Isolation by geographical barriers arose during Pleistocene in the western Peloponnese were the source of the evolution of the two reciprocally monophyletic subclades found in the S. keadicus mitochondrial clade, and the morphological differences found among the four populations. Along with the lack of structure in the nuclear genome in the three populations ascribed to S. peloponensis, this suggests an incipient speciation process occurring in these Squalius species in the western Peloponnese.